Exposure to inter-parental conflict across 10 years of the early childhood period: Data from the Longitudinal Study of Australian Children. - Brown, Stephanie; Nicholson, J; Westrupp, E; Westrupp, Elizabeth Mary; Rose, Natalie; Nicholson, Jan Maree (My University, 2015)
Rates of child exposure to inter-parental conflict are high and appear to be increasing, with at least one million Australian children affected annually. To-date, there is no established prevalence for inter-parental conflict that includes the more common but less severe forms for young families in the wider Australian community. The current study aims were to examine the prevalence, persistence, and the individual, family and socio-economic context of inter-parental conflict. Data were from four waves of the Baby (n = 4,898) and Kindergarten (n = 4,182) cohorts of the Longitudinal Study of Australian Children. Verbal and physical inter-parental conflict was measured using the Argumentative Relationship Scale. More than 1 in 3 mothers (35–36 %) reported any verbal and/or physical conflict. Prevalence of verbal conflict at each wave (10–13 %) was higher than physical conflict (4–10 %), with low co-occurrence (1–3 %). Report of inter-parental conflict at one wave only was most common (19 %); although 13 % of mothers reported conflict at two waves; and 5–6 % reported persistent conflict across three or more waves. Social disadvantage was consistently associated with report at one-wave only and persistent inter-parental conflict. Extrapolated to the Australian population, an estimated 1.9 million children are likely to be affected by inter-parental conflict within any 6 years of the early-to-middle childhood period. Establishing accurate prevalence and understanding the social context of the less severe but most common forms of inter-parental conflict will allow family and child support services to allocate finite resources more effectively and develop targeted interventions to promote children’s positive development.
Keywords: Life Events; Children -- Outcomes; Families -- Parents and Parenting; Disadvantage, adversity and resilience; Families and relationships; Life Events; Families; Children; Parents and Parenting; Outcomes; Dsiadvantage, adversity and resilience; Families and relationships; Adversity and resilience